MAGNESIUM SULPHATE VERSUS PHENYTOIN FOR ECLAMPSIA: ONE YEAR PROSPECTIVE STUDY - Mona Sharma; R Koirala; U Sharma; P Singh; S Gupta (Journal of Nepal Medical Association, 2003)
Aim: Eclampsia is one of the important preventable causes of maternal mortality. This study aims to review the clinical profile of eclamptic women and compare the maternal mortality, recurrence of convulsions, other morbidities including the neonatal outcome with Magnesium Sulphate versus Phenytoin used for its management. Material and Methods: Prospective study was carried out in all the eclamptic patient admitted in Gynae ward from April 2000 - April 2001 (Baisak 2057 to Chaitra 2057). Results: There were total of 30 patients.Most of the them (53.3%) were of the 15-20 years of age group and three fourth (73%) were primigravidas. More than half (56%) were unbooked and one fourth were nonimmunised and illiterate .Blood pressure had never been measured in 63% of the patient . In the Phenytoin Group 68.75% had recurrences of fits where as in the Magnesium Sulphate Group only 21.43 % had reccurence. In the Magnesium Sulphate group, 50% delivered normally whereas 42.5% needed caesarean section in the Phenytoin group Only 6.2% delivered normally and in 37.5 % forceps had to be applied. There were 37.50% admission to Neonatal Intensive Unit (NICU) for various complications in Phenytoin group whereas there were only 14.2% NICU admission in Magnesium Sulphate group. There were two cases of neonatal deaths out of 16 neonates in the Phenytoin group whereas only one out of 14 cases in Magnesium Sulphate group. There was only one maternal death in these thirty patients and it belonged to the Phenytoin group. Conclusion: As proved in many other studies this study also showed that Magnesium Sulphate was superior to Phenytoin in terms of recurrence of fits, maternal and neonatal outcome. In our country where many deaths still occur due to Eclampsia the valuable role of magnesium Sulphate should not be ignored and health personnels should be trained for its frequently than it is practiced to-day.